The Archaeology of Fazzan, Volume 4 Survey and Excavations at Old Jarma (Ancient Garama) carried out by C. M. Daniels (1962-69) and the Fazzān Project (1997-2001) - Mattingly, David J. (2013)
This is the concluding volume of the Archaeology of Fazzān series, bringing to press the combined results of two Anglo-Libyan projects in southern Libya: the pioneering work of Charles Daniels between 1958 and 1977 and the Fazzān Project directed by David Mattingly between 1997 and 2001. The investigations carried out by these two projects allow an entirely new reconstruction and understanding of the historic desert societies of the Libyan Sahara. In particular, the work has shed light on the ancient people known to Greco-Roman writers as the Garamantes, who are now revealed to have been a sophisticated state, with permanent towns and villages and an economy based on oasis agriculture and Saharan trade. This volume presents the results of excavations and survey work at the site of Old Jarma, identifiable with the Garamantian capital, Garama, that also had a long after-life in Medieval and Early Modern times. The Fazzān Project revealed an extraordinary urban story, spanning 10 major construction phases that extended from c.400 BC to the AD 1930s. The detailed publication of the complex stratigraphic evidence and the accompanying finds assemblages opens a fascinating window on the cultural heritage and lifeways of a central Saharan oasis.